The Digestibility and Bacterial Growth Rates of Microwave Treated Sago (Metroxylon sagu) Starch - Mohd Alhafiizh, Zailani; Hanisah Kamilah, Abd Razak; Ahmad, Husaini; Awang Zulfikar Rizal, Awang Seruji; Shahrul Razid, Sarbini (Universiti Putra Malaysia Press, 2023)
Sago starch is rich in resistant starch (RS) but less utilised than other commercial starches. Hence, modification is essential to give an add-on value to the starch. Thus, the objective was to determine the influence of microwave heat treatment (MHT) on the digestibility and probiotic growth rates of sago starch. In this study, the starch was treated by MHT for durations of up to 20 min. The digestibility and bacterial growth rates increase as the treatment duration increases to 15 min. It implies the potential of the MHT in increasing the digestibility of the sago starch and improving its prebiotic property based on probiotic growth rates.